The LIM-Homeodomain Protein Islet Dictates Motor Neuron Electrical Properties by Regulating K(+) Channel Expression - Wolfram, Verena (Cell Press, 2012)
Neuron electrical properties are critical to function and generally subtype specific, as are patterns of axonal and dendritic projections. Specification of motoneuron morphology and axon pathfinding has been studied extensively, implicating the combinatorial action of Lim-homeodomain transcription factors. However, the specification of electrical properties is not understood. Here, we address the key issues of whether the same transcription factors that specify morphology also determine subtype specific electrical properties. We show that Drosophila motoneuron subtypes express different K(+) currents and that these are regulated by the conserved Lim-homeodomain transcription factor Islet. Specifically, Islet is sufficient to repress a Shaker-mediated A-type K(+) current, most likely due to a direct transcriptional effect. A reduction in Shaker increases the frequency of action potential firing. Our results demonstrate the deterministic role of Islet on the excitability patterns characteristic of motoneuron subtypes.